(untitled) - Feather, John P. (London, 2013)
Explores the information revolution that continues to gather pace, as the understanding and management of information becomes even more important in a world where data can be transmitted in a split second. The social web, or Web 2.0, is now embedded in daily life, and some of its applications have become the most popular forms of communication system. Even the predominance of e-mail -- one of the most familiar manifestations of the information revolution -- is now threatened by texting and the use of such applications as Twitter. The ways in which we expect to interact with information -- and how much we are willing to pay for access to it -- are throwing up new opportunities and debates. At a societal level, as the quantity of personal digitized information continues to grow exponentially, so do both the benefits of exploiting it and the dangers of misusing it. The use of information and communications technology (ICT) to make government more accessible has to be more vigilant or more intrusive, according to one's point of view. Behind all of this lies further technical change: the massive expansion of connectivity to high-speed broadband networks; the phased abandonment of analogue broadcasting; and above all the widespread availability and use of sophisticated multi-functional mobile devices which carry voice, video, and data and which can themselves be carried anywhere. The implications for daily life, for education, for work, and for social and political relationships are massive.
Keywords: Xã hội thông tin,Information society